The potential role of night-time lighting in attracting terrestrial insects as food for Oreochromis mossambicus and Clarias gariepinus (Tropical Zoology, 2017)
This study investigated the potential of night-time lighting in enhancing the utilization of aerial insects by Oreochromis mossambicus and Clarias gariepinus. Six treatments L0 (Light with no fish), N0 (No light, with no fish), LT (Light with O. mossambicus), NT (No light with O. mossambicus), LC (Light with C. gariepinus) and NC (No light with C. gariepinus) were randomly assigned to aquadams and replicated three times. Two hundred O. mossambicus (60±0.6 g) and 100 C. gariepinus (90±0.8 g) were stocked to assigned aquadams. Two other treatments designated FT (O. mossambicus fed on pellets) and FC (C. gariepinus fed on pellets), were added. SGR was higher (0.31 g/day) in O. mossambicus subjected to night-time lighting than those that were not (0.05 g/day). C. gariepinus under the night-time lighting also had a higher SGR (0.30 g/day) than the ones that were not (0.26 g/day). However, in both species the growth rate was lower when compared to those fed on commercial pellets. Oreochromis mossambicus benefited more from night-time lighting. The most abundant aerial insects were moths and beetles. The serial slaughter method was used to determine the gastric evacuation rate of moths and beetles in O. mossambicus and C. gariepinus. Moths were evacuated faster (−0.235) than beetles (−0.108) in O. mossambicus. In C. gariepinus, the gastric evacuation of moths was also faster (−0.40) than beetles (−0.36). This implies digestion efficiency was higher in moths than beetles. Water physico-chemical variables were analysed once a week and they were not affected by night-time lighting.